(3GdEYdGe aj hajGJ GdCYdGes - (3ESeGYjd Hf eMeO Hf HQOS GdHYdHcj, YeGO GdOjf CHh GdaOGA, GHf HQOS , J (B786 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3hHYO aEfi deG fXQJ aj cJGH GdJPcQI aj WHbGJ GdMaGX ddMaGX GdYOd TeS GdOjf CHj YHOGddg GdPgHj hLOJg bO PcQ ajgG CcKQ ef Cda MGaX s
(3BNQgG (B:s
(3hBdg hUMHg Cgd GdhaG hRGOge QH GdeYGdj TQaG s
(3GfXQ GjVG HQbe (B51 (3HQbe (B897 (3JGQjNs
(3GdfSNI HgG MhGTs
(3HgGeTgG TQhM hJYQja ddGYdGe GdhGQOI aj GdefXheIs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs